Plasma biomarkers for Alzheimer's disease: from amyloid to CNS derived extracellular vesicles, overview of changes through age, sex and risk factor in control and AD populations. (20th December 2022) - Boyer, Emilien; Kienlen‐Campard, Pascal; Hanseeuw, Bernard J
Abstract: Background: Hallmark proteins pathogenic in Alzheimer's disease (AD), amyloid and tau, can now be quantified in plasma samples using single‐molecule array (SIMOA). However, proteins are not only circulating in plasma, but are also present in nervous system‐derived extracellular vesicles (NDBEs) secreted by neurons in the plasma. We aim to quantify plasmatic NBDEs to evaluate whether their number or content are modified in symptomatic AD. Method: Plasma samples were obtained in clinically normal (CN) participants (N = 76, sex ratio F/M = 1.5, mean age 57.5 ± 16.3, Apoε4 positive n=31, Apoε4 negative n=43) and in patients with symptomatic AD (N=17, sex ratio F/M = 0.7, mean age 70.1 ± 7.6). Quantification of amyloid 42 – 40 peptides and Tau protein was achieved with SIMOA multiplex analysis. For relative quantification of NDBEs circulating in plasma, we used DELFIA ELISA immunoassay with anti‐neuronal cell adhesion molecule (NCAM1) antibody. Normalization to the total number of vesicles was done using an antibody targeting CD81, a ubiquitous vesicle marker. Result: We observed a significant decrease of Aβ42 in AD patients (p < 0.05), and in CN carrying an Apoε4 allele (p < 0.05). The ratio Aβ42/40 was lower in AD patients ( p < 0.05) and the ratio Tau/Aβ42 was higher ( p < 0.05). In CN, the relative amount of NDBEs in plasma was correlated with circulating Aβ42 ( p < 0.0001, R² 0.2699) and Tau ( p < 0.0001, R² 0.2753) such that greater numbers of NBDEs were associated with lower concentrations of proteins in circulating plasma. Amount of NDBEs do not seem to change with age, Apoε4 status or in AD patients. Conclusion: Levels of Ab42, ratios Aβ42/40 and Tau/Aβ42 in plasma are significantly different in patients with symptomatic AD, and between ApoE4 carriers and non‐carriers among CN individuals. However, the number of NBDEs is negatively associated with the concentrations of these proteins, suggesting that these proteins are encapsulated in NBDEs. Future work will analyze the content of the vesicles to confirm that hypothesis.